Implementation of Zachman Framework to Support Business Activities and Performance - Nurul Fadilah Aswar; Ilma Wulansari Hasdiansa; Andika Isma; Faslul Rahman; Muh. Yusuf Kholiq M (Global Research and Collaboration, 2024)
PT Suzuki Indomobil Motor (SIM) is a foreign investment company engaged in the business of Component Industry and Assembly of two-wheeled SUZUKI Brand motor vehicles (Motorcycles) and four wheels (Cars) which strives to provide solutions to the needs of transportation for the community by providing the principle of Total Solution, namely by providing the best service to consumers by combining synergies between technology and information systems. Building integrated systems within the company requires very careful and planned planning in order to pay attention to all stakeholders in the company. Planning the entire system including all aspects of the organization and business is what is known as Enterprise Architecture (EA). EA is used to analyze, integrate, and document the architecture in the enterprise. The increasingly effective and efficient utilization of IS and IT supports business activities, achieving One of the frameworks that addresses issues in the development of information systems in the company from various points of view is the Zachman Framework. Increasingly effective and efficient use of information systems (IS) and information technology (IT) that support business activities to achieve organizational goals and services for stakeholders. This goal is expected to be achieved optimally if there is synergy between the SI and IT strategies and the IT strategy.